2018
DOI: 10.1097/gox.0000000000001764
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Presurgical Nasoalveolar Molding on the Midface Symmetry of Children with Unilateral Cleft Lip and Palate: A Long-term Follow-up Study

Abstract: Background:Midface symmetry is an important indicator of success of complete unilateral cleft lip and palate (CUCLP) treatment. There is little literature on the long-term effects of presurgical nasoalveolar molding (PNAM) on midface symmetry in children treated for CUCLP. This study aimed to compare children with CUCLP who underwent PNAM before surgical interventions, children who did not receive PNAM, and age- and sex-matched controls in terms of midface symmetry.Methods:We evaluated 39 frontal facial photog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A total of 439 publications were identified, and 13 publications met criteria for inclusion in this review (Figure 1) (Barillas, 2009; Chang et al, 2010; Clark, 2011; Shetty, 2017; Akarsu-Guven, 2018; AlHayyan et al, 2018; Kornbluth, 2018; Massie, 2018; Peanchitlertkajorn, 2018a; Peanchitlertkajorn, 2018b; Singer, 2018; Funayama et al, 2019). The fully reproducible search strategy is included in the Online Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 439 publications were identified, and 13 publications met criteria for inclusion in this review (Figure 1) (Barillas, 2009; Chang et al, 2010; Clark, 2011; Shetty, 2017; Akarsu-Guven, 2018; AlHayyan et al, 2018; Kornbluth, 2018; Massie, 2018; Peanchitlertkajorn, 2018a; Peanchitlertkajorn, 2018b; Singer, 2018; Funayama et al, 2019). The fully reproducible search strategy is included in the Online Appendix.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial skeletal changes take place during infancy, and the landmark points on bone may change significantly between the affected and control sides as the child grows. AlHayyan et al (2018) reported a long-term study of skeletal changes achieved using the NAM method over a period of 5 years. According to their study, the In a previous study, we compared the shape of the nostrils at 1 month after the primary cheiloplasty between a group of patients who received treatment using the NAM method and another of patients treated using a conventional appliance (Sasaki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…AlHayyan et al described no significant impact on long-term midface symmetry of presurgical NAM in children with UCLP when compared with children treated without any form of presurgical infant orthopedics. 17 Furthermore, some studies describe a relapse of initially good results. We are not able to prove or disprove these observations with our presented study but clinically agree that in some cases a relapse might be observed.…”
Section: Discussionmentioning
confidence: 99%
“… 14 – 16 More recently, favorable long-term results have been described, revealing a previously described assumption that NAM therapy might reduce the need for secondary corrections. 7 , 11 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%